IMPROVING PHYSICAL LITERACY AND EXERCISE AWARENESS FOR TEACHERS AND ELEMENTARY SCHOOL STUDENTS THROUGH THE CAKRAM RAGA TRAINING PROGRAM IN BANJARMASIN - Raden Argarini dr., M.Kes., Ph.D.; Hayuris Kinandita; Lilik Herawati; Ulul Azmy; Rafi Arofah Dirgantari; Wahyu Renandi Aji; Laila Ramadhani (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
An active society plays a crucial role in enhancing physical fitness, productivity, and overall quality of life. Data from the Ministry of Youth and Sports (Kemenpora) in 2023 indicated a steady decline in sports participation from 2021 to 2023. South Kalimantan ranks second lowest nationwide, with only 16.67% participation and an index score of 0.167. Furthermore, more than 77.13% of Indonesian children and adolescents aged 10 to 15 years were classified as having “low” or “very low” fitness levels. These conditions underscore the urgent need for health promotion through physical activity to support the Indonesia Emas 2045 vision. This community engagement program aimed to increase sports participation among school-age children in Banjarmasin through the innovative educational media CAKRAM RAGA (Sports Reference Disc) and educational videos. This educational media provides several options for physical exercise for children, allowing teachers and students to select a package of exercises for their daily exercise program. The training was conducted in the form of a seminar and workshop, during which participants were trained to use the CAKRAM RAGA media. The program took place on August 21–22, 2025, and involved physical education teachers, classroom teachers, and students, in collaboration with STIKES Suaka Insan Banjarmasin, with a total of 46 participants. Evaluation results demonstrated an improvement in participant knowledge regarding recommended physical activity, sport injury prevention, and nutrition for children, with the mean pre-test score increasing from 87.85 to 89.63 on the post-test. Although the improvement was only about 2%, it indicated that participants already had a strong baseline understanding, and the activities effectively reinforced existing concepts. Overall activity evaluation results showed that 98% of respondents strongly agreed that CAKRAM RAGA was easy to understand and use, while 94% strongly agreed that it was suitable for implementation in schools. Moreover, 98% expressed motivation to encourage daily student exercise after recognizing its importance. In conclusion, the implementation of the innovative educational media CAKRAM RAGA proved to be effective, user-friendly, and received highly positive feedback from participants. It is recommended that similar programs be expanded to more schools to broaden their benefits and promote an active, healthy generation in support of Indonesia Emas 2045.